Craniofacial multi-point fascial suspension combined with tongue-shaped flap for correction of cryptotia deformity. Issue 9 (September 2022) - Cai, Siyuan; Chen, Zaihong; Cai, Zhen; Luo, Kexian; Cui, Wei; Sheng, Yang; Zhang, Liyuan; Chen, Youxin; Lin, You
Summary: Background: In this article, we will introduce a modified surgical approach to correct cryptotia (by suspending the auricular cartilage to the temporal region), which allows for a more visible and consistent surgical benefit than previous techniques that simply used flap accumulation. Methods: We use several stitches to suspend the released auricular cartilage from the root of the auricular cartilage (approximately deep in the cavum conchae and the cymba conchae cartilage) to the temporal bone periosteum in a higher position, presumably similar to the principle of leverage, thus obtaining a larger auriculocephalic sulcus and a higher superior auricular pole. Results: Over the past 5 years, this new technique was applied to the auricles of 20 patients between the ages of 15 and 40 years. They all obtained a satisfactory height of the upper pole of the auricle, the auriculocephalic sulcus, and the amount of skin tissue behind the auricle. Conclusions: In response to the failure of previous techniques to provide a satisfactory auriculocephalic sulcus and superior auricular pole height, this modified technique provides more consistent support directly to the auricle by means of suspension, allowing for a deeper head sulcus and higher superior auricular pole. The main features of this technique are the convenience and stability of the results, and the ability to adjust the sulcus and the height of the auricle as needed during the surgery.